Transcriptome and QTL mapping analyses of major QTL genes controlling glucosinolate contents in vegetable- and oilseed-type Brassica rapa plants - Kim, Jin A.; Moon, Heewon; Kim, Hyang Suk; Choi, Dasom; Kim, Nan-Sun; Jang, Juna; Lee, Sang Woo; Baskoro Dwi Nugroho, Adji; Kim, Dong-Hwan (Frontiers in Plant Science, 2023)
Glucosinolates (GSLs) are secondary metabolites providing defense against pathogens and herbivores in plants, and anti-carcinogenic activity against human cancer cells. Profiles of GSLs vary greatly among members of genus Brassica. In this study, we found that a reference line of Chinese cabbage (B. rapa ssp. pekinensis), ‘Chiifu’ contains significantly lower amounts of total GSLs than the oilseed-type B. rapa (B. rapa ssp. trilocularis) line ‘LP08’. This study aimed to identify the key regulators of the high accumulation of GSLs in Brassica rapa plants using transcriptomic and linkage mapping approaches. Comparative transcriptome analysis showed that, in total, 8,276 and 9,878 genes were differentially expressed between ‘Chiifu’ and ‘LP08’ under light and dark conditions, respectively. Among 162 B. rapa GSL pathway genes, 79 were related to GSL metabolism under light conditions. We also performed QTL analysis using a single nucleotide polymorphism-based linkage map constructed using 151 F5 individuals derived from a cross between the ‘Chiifu’ and ‘LP08’ inbred lines. Two major QTL peaks were successfully identified on chromosome 3 using high-performance liquid chromatography to obtain GSL profiles from 97 F5 recombinant inbred lines. The MYB-domain transcription factor gene BrMYB28.1 (Bra012961) was found in the highest QTL peak region. The second highest peak was located near the 2-oxoacid-dependent dioxygenase gene BrGSL-OH.1 (Bra022920). This study identified major genes responsible for differing profiles of GSLs between ‘Chiifu’ and ‘LP08’. Thus, our study provides molecular insights into differences in GSL profiles between vegetative- and oilseed-type B. rapa plants.